ANALISIS AUDIT REPORT LAG PADA PERUSAHAAN SEKTOR MANUFAKTUR - Reynaldi Gema Pamungkas; Pipit Mutiara (Jurnal Financia : Akuntansi dan Keuangan, 2021)
Audit Report Lag is the length of the audit completion time measured from the closing date of the fiscal year or the end of the fiscal year until the date of the issuance of the audited financial statements. This study aims to examine the influence of the audit committee, company size, profitability and solvency of the company in predicting audit report lag in mining sector companies listed on the Indonesia Stock Exchange 2016-2018. The data analysis technique used descriptive verification method. The results of this study indicate that partially company size and solvency had a significant effect on audit report lag; meanwhile the audit committee and profitability had no effect on audit report lag. Audit Committee, company size, profitability and solvency simultaneously had a significant effect on audit report lag of 26.48% in mining sector companies listed on the Indonesia Stock Exchange in 2016-2018.